Single-nucleotide polymorphisms in genes related to oxidative stress and ion channels in chickens are associated with semen quality and hormonal responses to thermal stress. (April 2022) - Zhuang, Zi-Xuan; Chen, Shuen-Ei; Chen, Chih-Feng; Lin, En-Chung; Huang, San-Yuan
Abstract: Heat stress causes economic loss of livestock industry in tropical areas. Exploring genetic markers for selection of thermotolerance will benefit chicken production. Oxidative stress and fluid–salt balance are tightly associated with thermotolerance and productivity in domestic animals. The study aimed to identify single-nucleotide polymorphisms (SNPs) in genes related to oxidative stress and ion-channel regulation and their associations with semen quality and hormonal responses. In total, 28 SNPs within 11 candidate genes were identified to associate with hormonal changes and semen quality in both broiler- and layer-type Taiwan country chickens (TCCs) after exposure to acute heat stress at 38 °C for 4 h. Acute heat stress significantly affected plasma levels of triiodothyronine and corticosterone and reduced sperm motility, viability, and concentrations in both strains at Day 1 after exposure. In the B-strain TCCs, five SNPs within NDUFA8 and DAB2IP had significant effects on plasma adrenaline and corticosterone levels, and six SNPs within TRPC1, SLC9A9, and TRPC7 markedly affected plasma corticosterone and triiodothyronine levels. In the L2 strain, 15 SNPs within PSMA2, TPK1, MTF1, and CUL1 exerted effects on plasma corticosterone and triiodothyronine levels. Five SNPs within CUL3, TRPC1, and SLC9A9 in the B strain and two SNPs within MTF1 in the L2 strain were associated with sperm concentrations at Day 1 after exposure to heat stress. In conclusion, acute heat stress impaired semen quality and altered plasma corticosterone and triiodothyronine levels in TCCs. Some SNPs involved in oxidative stress and ion-channel regulation were identified to associate with the hormonal and semen alterations. These SNPs in conjunction with differential hormonal responses and semen quality serve as genetic markers for thermotolerance selection in sire lines of chickens. Highlights: This study analyzed the effect of SNPs in candidate genes on chickens under heat stress. SNPs at oxidative stress-related genes associate with plasma hormonal changes and affect semen quality. SNPs at ion channel-related genes affect plasma hormone levels and sperm concentrations.